New Variant of Esophageal Atresia - Harne, Swapnil; Pathak, Manish; Rattan, Kamal Nayan (Journal of Neonatal Surgery, 2016)
Esophageal atresia with tracheoesophageal fistula (EA/TEF) associated with distal congenital esophageal stenosis (CES) is a well-known entity. We encountered three patients of EA/TEF associated with long and unusual CES.